Mapping internet coverage in Malaysia’s university campuses: a case study of the Sultan Idris Education University, Perak - Nasir Nayan,; Mohmadisa Hashim,; Yazid Saleh,; Hanifah Mahat, (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
ICT revolution has brought changes in the lifestyle of all walks of life including that of the university students. More than ever, the use of information and communications technology is now not only closely linked to higher education but is also imperative to the shaping of that first-class mind fit to function in the present globalization era. The Malaysian government through the Malaysian Communications and Multimedia Commission has regularly maintained its policy to provide quality internet coverage throughout the nation. This study examined student Wi-Fi accessibility at the Universiti Pendidikan Sultan Idris (UPSI) through geographic information system (GIS) mapping in order to establish the Wi-Fi coverage areas for the students. The data employed were Wi-Fi accessibility observations at the identified locations using a tool known as Wi-Fi analyzer included in the mobile phone. That data were subsequently manipulated in the GIS through ArcGIS 9.3 software. Then, kriging interpolation technique was used to form a coverage area that was divided into four types: strong, medium, weak and very weak. The findings showed that more than 80 percent of the coverage was weak or very weak, pointing to the necessity of providing higher levels of campus-wide internet coverage for the benefit of the students.